A comparative study of educational provision for children with neurogenetic syndromes: parent and teacher survey. (17th July 2015) - Reilly, C.; Senior, J.; Murtagh, L.
Abstract: Background: A number of neurogenetic syndromes have a high association with special educational needs including fragile X syndrome (FXS), Prader–Willi syndrome (PWS), Williams syndrome (WS) and Velo‐Cardio‐Facial syndrome (VCFS). There is a paucity of research on educational provision for children affected by these syndromes. Method: Parents (n = 381) and teachers (n = 204) of school‐aged children with one of the four syndromes in the UK and Ireland were surveyed in a range of areas concerning the child's educational provision. Areas surveyed included school placement, views on the needs of children with the syndromes, desired changes to current provision and perceived teacher knowledge. Results: School placement in mainstream settings decreased with age in all of the syndromes. Males with the syndromes were more likely to be in specialised educational settings with the exception of WS. Teachers reported limited input on initial or subsequent training for all of the syndromes. The majority of teachers did not view the needs of children with syndromes as different from other children with intellectual disability (ID) although there were significant differences between the syndromes. Changes deemed necessary to provision by parents and teachers differed between the syndromes indicating the existence of perceptions of syndrome specific needs. The lowest perceived level of teacher knowledge was in the VCFS group. Conclusion: The majority of teachers of children with neurogenetic syndromes report limited knowledge of the syndromes, but also a lack of belief that the children's needs are different from the majority of children with ID. Differences between the syndromes in some areas of provision suggest that a child's syndrome does impact on educational provision in some areas.